The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/0034-7167-2019-0736
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome prevalence among nursing technicians of an Adult Intensive Care Unit

Abstract: Objective: to verify Burnout Syndrome prevalence among nursing technicians of an adult Intensive Care Unit and associate prevalence with sociodemographic and clinical data. Method: a cross-sectional study carried out in an adult Intensive Care Unit of a large public hospital in southern Brazil, between March and April/2018. Prevalence was assessed using the Maslach Burnout Inventory. Results: 122 nursing technicians participated (aged 39±2.5 years), 76% being women. Burnout Syndrome prevalence was 19.7% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(47 reference statements)
0
2
1
7
Order By: Relevance
“…Another study showed that women in nursing had a higher risk of negative impact on mental health ( 32 ) . In the present study, none of the demographic variables of the participants showed a significant difference for occurrence of Burnout Syndrome: most of the participants were women (79; 85.87%), whose is common among nursing professionals in health services in Brazil ( 10 , 23 , 33 - 34 ) , professional experience (65.22% had graduated over 11 years ago) and age (mean of 42 years). These characteristics may be related to a greater personal and professional maturity.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Another study showed that women in nursing had a higher risk of negative impact on mental health ( 32 ) . In the present study, none of the demographic variables of the participants showed a significant difference for occurrence of Burnout Syndrome: most of the participants were women (79; 85.87%), whose is common among nursing professionals in health services in Brazil ( 10 , 23 , 33 - 34 ) , professional experience (65.22% had graduated over 11 years ago) and age (mean of 42 years). These characteristics may be related to a greater personal and professional maturity.…”
Section: Discussioncontrasting
confidence: 67%
“…Each dimension is divided into three levels, according to the sum of the items: high, moderate, and low. For Emotional Exhaustion: ≥27: high level, from 19 to 26: moderate, and ≤18: low level; Depersonalization: ≥10: high level, from 6 to 9: moderate, and ≤5: low level; and Professional Accomplishment: ≥40: high level, from 34 to 39: moderate, and ≤33: low level ( 22 - 23 ) . At the end of the MBI-HSS instrument, there were questions about the impact of the COVID-19 pandemic on Burnout Syndrome levels, with Yes and No alternatives.…”
Section: Methodsmentioning
confidence: 99%
“…Das cinco pesquisas sobre a síndrome de Burnout (SB), duas contam com uma amostra superior a 100 participantes: o artigo de Silva et al (2015), que verifica a prevalência de 55,3% de SB em 130 profissionais de equipes de enfermagem de UTI 43 ; e a pesquisa de Alves et al (2021), que identifica a prevalência de 62,9% em 122 técnicos de enfermagem de UTI 7 . Ambos os dados são referentes ao critério de Grunfeld et al 47 .…”
Section: Síndrome De Burnoutunclassified
“…Terapia Intensiva (UTI) tornaram-se especializadas em desempenhar um papel fundamental na sobrevida de pacientes gravemente enfermos que exigem cuidados especializados e vigilância constante. No que diz respeito a serviços de saúde, estas são essenciais na prática da medicina moderna [4,5].…”
Section: Com O Avanço Das Práticas Médicas E Aparatos Tecnológicos As...unclassified
“…A humanização da assistência em Enfermagem na Terapia Intensiva, à luz da Teoria de Wanda Horta classifica as necessidades humanas em 3 grandes dimensões: psicobiológicas; psicossociais e psicoespirituais. Conclusão: A formação dos profissionais deve ser pautada nas raízes da Enfermagem por meio de suas teorias para Enfermagem Brasil 2022;21 (5):680-689 03 grandes dimensiones: psicobiológicas; psicosocial y psicoespiritual. Conclusión: La formación de profesionales debe partir de las raíces de la Enfermería a través de sus teorías para reconocer y utilizar su ciencia hoy como construcción del cuidado humanizado en Enfermería.…”
Section: Introductionunclassified